Behavioural-Based Assessments in the Special Forces Environment: A Procedural Review - Van Wyk, Stephanie; du Toit, Renier (Scientia Militaria - South African Journal of Military Studies, 2019)
The South African Special Forces is a grouping of highly trained, motivated and dedicated soldiers who execute specialised tasks that ordinary infantry soldiers are not trained or required to conduct. The milieu in which Special Forces operators function is notoriously challenging as these forces could deploy for a few days or several months or longer in any type of environment. It is therefore essential that the correct candidates be selected to function in these environments. The aim of the officer’s potential assessment (OPA) is thus to select candidates with the physical, cognitive, emotional and psychological fitness to be trained as South African Special Forces operators and officers. The study on which this article is based, explored the development of the behavioural assessments during the South African Special Forces officers’ selection process as a method and model for the review and design of assessment centres from a holistic, detailed perspective.